Effects of the deficiencies of macronutrients in two soybean (Glycine max (L.) Merr.) varieties, Santa Rosa and UFV-1 grown in nutrient solution - Malavolta, E.; Vidal, A.A.; Gheller, A.C .; Fancelli, A.L.; Kishimo, A.Y.; Piza Jr., C. Toledo; Santos, D.B.; Ruy, V.M.; Faquimo, V.; Eimori, I.E.; Guimares, P.T.G.; Ortiz, O.B.; et al. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1980)
Two soybean varieties were grown in nutrient solution in the presence and in conditions of deficiency of macronutrients (supplied at 1 tenth of full strength level). During the life cycle samples were taken for leaf analyses, as well as for the determination of the activity of nitrate reductase (NO3R). At the end of the pod filling, periodical mineral analyses were carried out in all the organs of the plants under the "complete" tratment; only leaves were analysed in teh remaining plants. The main conclusion were the following (1) symptoms of deficiency which showed up (N, P, K and Ca) are in agreement with those described in the literature; (2) plants deficient in N,P, K or Ca did not produce any pods; (3) there was a differential response in quantitative terms, of the two varieties to the deficiency of elements in the substrate; (4) the adequate levels of N, P, K, Ca, Mg and S are not the same for the two varieties; (5) quick tests provided and indication of the nutritional status; (6) NO3R activity reflected the level of N in the nutrient solution.